2019
DOI: 10.1530/edm-19-0073
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma arising from an ectopic adrenal tissue in multiple endocrine neoplasia type 2A

Abstract: Summary A 21-year-old woman was referred to our hospital to treat bilateral pheochromocytomas (PCCs) after a diagnosis of multiple endocrine neoplasia type 2A (MEN2A). We performed bilateral laparoscopic adrenalectomy. One year after the operation, urinary fractionated metanephrines in 24-h urine increased. MRI showed a 30 mm tumor on the interaortocaval region and 123I-MIBG concentrated in this area. We excised the tumor and performed para-aortic lymphadenectomy. Histopathologic examination confirmed a PCC ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Both cortex and medulla can be present in the ectopic adrenal tissue, if the separation takes place in a later phase during organogenesis, after the neural crest's migra- tion into the cortex. Usually, the medulla might be found in the ectopic tissue when the separation takes place near the location of the normal adrenal glands [7,[12][13][14][15]. Pheochromocytoma can be sporadic or hereditary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cortex and medulla can be present in the ectopic adrenal tissue, if the separation takes place in a later phase during organogenesis, after the neural crest's migra- tion into the cortex. Usually, the medulla might be found in the ectopic tissue when the separation takes place near the location of the normal adrenal glands [7,[12][13][14][15]. Pheochromocytoma can be sporadic or hereditary.…”
Section: Discussionmentioning
confidence: 99%
“…Korpershoek et al showed that MEN2-associated pheochromocytoma exhibits genomic alterations identical to adrenal medullary hyperplasia in MEN2 syndrome, suggesting that adrenal medullary hyperplasia could represent a precursor lesion for pheochromocytoma [13]. Recently, Ohsugi et al described a case of bilateral adrenal pheochromocytoma associated with ectopic adrenal medullary hyperplasia that 12 months later developed into a pheochromocytoma, in a patient with MEN2A syndrome [14]. All patients with a diagnosis of pheochromocytoma should be considered for genetic screening [6,16].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction between adrenal chromaffin cells and cortex is essential for the maturation of adrenal medulla, whereas the Zuckerkandl organ, the largest extra-adrenal chromaffin accumulation in mammals, lacks such interaction with steroidogenic tissue and undergoes involution after birth (postnatal autophagy-mediated cell death) in the absence of cortex-derived glucocorticoids ( 14 ). This appears to be the reason for the absence of literature describing ectopia of adrenal medulla only, that is not surrounded by cortex, while entities related to adrenal or extra-adrenal chromaffin cells (pheochromocytoma and paraganglioma), and even pheochromocytoma in ectopic adrenal gland have been reported ( 15 , 16 ).…”
Section: Ectopic Adrenal Tissues Contain Either Cortex Only or Both C...mentioning
confidence: 99%
“…In another case, pheochromocytoma arising from ectopic adrenal tissue was presented in a 21-year-old woman with multiple endocrine neoplasia type 2A showing that, not only the cortex but also the medulla can be found in ectopic adrenal tissue, even leading to a neoplasia. 16 According to data, functional hypertrophy may develop in ectopic adrenal tissue after removal or destruction of normal adrenal glands. 1 Also, cases of Cushing's syndrome or primary aldosteronism arising from ectopic tissue located in the appendix may mimic carcinoid tumor.…”
Section: Cases In Womenmentioning
confidence: 99%